Environmental Waste Management System in Effort Creates Sustainable Semarang - Carlito Da Costa; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Environmentally sound waste management is an area of Semarang city government efforts to manage the waste. The existence of good waste management, will make a sustainable environment in accordance with Act No. 18 Of 2008 on Waste Management. Research methodssociological jurisdiction is law as the law in action, described as an empirical social phenomena. The findings of the study (1) Implementationwaste management in the city of Semarang has been carried out by means of environmentally sound The program concept of 3R (Reduce, Reuse, Recycle), in cooperation with PT. Narpati Agung Lestari Karya Persada (2) Barriers to the realization of environmentally sound waste management systems, barriers: factors of population, The quality and quantity of human resources (HR) is still inadequate, operational factors. Solution: Conduct a training program, the training of human resources, increase its fleet of waste management.Keywords :Waste Management; Act No. 18 In 2008; A Sustainable City.